2012
DOI: 10.1007/s12032-012-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired apoptosis of megakaryocytes and bone marrow mononuclear cells in essential thrombocythemia: correlation with JAK2V617F mutational status and cytoreductive therapy

Abstract: Essential thrombocythemia (ET) is a clonal myeloproliferative disorder characterized by overproduction of megakaryocytes (MKCs) and platelets. The recent discovery of the JAK2 mutation has shed a new light on the development of ET but its pathogenesis still remains unknown. One of the possible mechanisms can be deregulation of apoptosis, resulting in accumulation of bone marrow MKCs. In this study, we investigated the apoptotic profile, as well as the expression of apoptosis-regulating protein in MKCs and bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We also found up-regulation of proapoptotic Bax protein in both HEL and SET-2 cells. In our previous study, we found that patients with essential thrombocythemia positive for the JAK2V617F mutation had markedly higher Bax expression than JAK2V617F negative cases [25]. As reported before, Mcl-1 protein has a crucial role in regulating the survival of hematopoietic stem cells [26].…”
Section: Discussionmentioning
confidence: 69%
“…We also found up-regulation of proapoptotic Bax protein in both HEL and SET-2 cells. In our previous study, we found that patients with essential thrombocythemia positive for the JAK2V617F mutation had markedly higher Bax expression than JAK2V617F negative cases [25]. As reported before, Mcl-1 protein has a crucial role in regulating the survival of hematopoietic stem cells [26].…”
Section: Discussionmentioning
confidence: 69%
“…In PV and ET patients it is very important to identify those whose risk of vascular and thrombotic complications is high enough to justify the use of risk-adapted treatment strategies, including aspirin, anticoagulants, hydroxyurea (HU), anagrelide, interferon alfa (IFN-alpha) or the recent JAK2 inhibitors (e.g., Ruxolitinib) (36). Patients are stratified and treatment is prescribed according to evaluation of the three major risk factors for thrombosis, namely previous history of arterial or venous thrombosis, possible presence of JAK2 mutation and age >60 years (36,38). The risk of thrombosis in older JAK2-unmutated patients without thrombosis history is low enough to occasionally consider, on an individual basis, skipping cytoreductive therapy (36).…”
Section: Introductionmentioning
confidence: 99%
“…HU is widely used as first-line cytoreductive therapy in 'high risk' patients, as result of consensus of randomized clinical trials (37,38). This drug is an antimetabolite, capable of inhibition of ribonucleoside diphosphate reductase necessary for synthesis and repair of DNA, with a subsequent myelosuppressive activity (38). Moreover, HU affects polymorphonuclear leukocytes function and interferes in their interactions with platelets, having an antithrombotic effect (38).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The pathobiological basis underlying these numerical and morphological megakaryocytic abnormalities is thought to result from multiple molecular disruptions promoting proliferation and enhancing survival. [9][10][11][12][13] These megakaryocytes have impaired death mechanisms conferred by overexpression of antiapoptotic Bcl-XL and reductions in pro-death BNIP-3. 9 11-13 These changes are universal in the MPNs but there are differences between entities.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have identified that apoptotic signalling processes are disrupted in megakaryocytes of the MPNs. [9][10][11][12][13] We intended to further delineate the biological basis of the apoptotic disturbances affecting megakaryocytes in the MPNs by assessing several biomarkers implicated in the intrinsic and extrinsic apoptotic pathways. We demonstrate through immunohistochemical analyses of human MPNs that the enhanced survival of myeloproliferative megakaryocytes occurs through inhibition of intrinsic death effectors despite concurrent extrinsic apoptotic activation.…”
Section: Introductionmentioning
confidence: 99%